Simulação como ferramenta para aplicação do MFV - Bekesas, Luiz Claudio (2012)
Value Stream Mapping (VSM) is a tool that has been used in lean manufacturing to redesign production systems in several industrial sectors. As part of lean principles, the VSM is a pictorial technique used to identify several kinds of wastes existing in the manufacturing floor and enables an e asy way to visualize possible alternatives to eliminate them. The company considered for this research is a traditional manufacturer of industrial gearboxes and auto parts, who has been using the VSM to locate and eliminate wastes for a family of products. This paper proposes the utilization of ProModel® 7.0 software as a simulation tool to build-up and to evaluate several alternatives for the future state value stream map (FSVSM). As a result it is possible to conclude that simulation represents a valuable strategy to obtain an optimized solution for the FSVSM, as it allows the analysis of several alternatives for several manufacturing indicators.